Calciotropic Principle of Solanum glaucophyllum in Broiler Chickens - Rovegno, S.; Miccoli, F.; Dallorso , M.; Iglesias, B.; Azcona, J. (International Journal of Poultry Science, 2012)
Solanum glaucophyllum (duraznillo blanco), which causes calcinosis of cattle in Argentina, contains the active metabolite of vitamin D3 either free or conjugated with carbohydrates as 1,25-(OH)2 vitamin D3-glycoside. Economic relevance of S. glaucophyllum could be seen as being the causal factor of toxicosis of grazing cattle and also as a valuable source of vitamin D3 active metabolites. Some pharmacological applications in human and veterinary medicine as well as in animal husbandry, have been assayed. The calciotropic principle was thought to be the main active metabolite of vitamin D3, once liberated from its glycoside. However, calciotropic activity of this glycoside seems to be feasible. In order to know the fate of the water soluble calciotropic principle of Solanum glaucophyllum administered orally to broilers, 1,25-(OH)2 vitamin D and 1,25-(OH)2 vitamin D3-glycoside plasma levels were assayed over a period of 24 hrs after a unique administration of the aqueous extract of the plant. Here we show that 1,25(OH)2 vitamin D plasma levels did not increase, while 1,25(OH)2 vitamin D3-glycoside rapidly appeared in blood, remained in circulation during the first 6 hrs and was undetectable 24 hrs after a unique oral administration of S. glaucophyllum (0.11 g DM/kg BW), to finishing broilers.